The taxonomic identity of the monocle bream Scolopsis vosmeri species complex (Perciformes: Nemipteridae), with comments on molecular phylogenetic relationships within the genus Scolopsis - Russell, Barry C.; Bogorodsky, Sergey V.; Mal, Ahmad O.; Bineesh, K.k.; Alpermann, Tilman J. (Zootaxa, 2022)
The monocle bream Scolopsis vosmeri species complex is revised. Three species in the complex are recognized: Scolopsis vosmeri (Bloch, 1792), widespread in the Indo-West Pacific, from the northern Indian Ocean (Pakistan, western India, Sri Lanka, Bay of Bengal, and the Andaman Sea, but not recorded from the Red Sea or Arabian Gulf, east African coast or Madagascar) to western Indonesia and Borneo; S. japonica (Bloch, 1793), restricted to the western Pacific Ocean from western Indonesia and north-western Australia east to the Philippines and north to southern Japan; and S. curite Cuvier, 1815, widespread from the western to the eastern Indian Ocean, including the Red Sea and Arabian Gulf. All three species are similar morphologically, and have been confused taxonomically, but phylogenetic analysis of the COI barcoding region shows they are evolutionarily divergent. The three species are redescribed in detail and characters found to distinguish them. Scolopsis vosmeri is easily distinguished from S. japonica and S. curite in having a white band along the side of the body; having a black spot  on most body scales (versus greenish yellow spot in S. japonica and S. curite); in lacking a distinct black spot (sometimes a small and faint spot present) on the upper pectoral-fin base (versus small black wedge-shaped spot present in S. japonica and S. curite); caudal peduncle whitish in live individuals (versus caudal peduncle usually yellowish in S. japonica and S. curite); and pelvic and anal fins crimson to orange-red (versus yellow in S. japonica and S. curite). Scolopsis japonica and S. curite are indistinguishable by color pattern but differ in the degree of spination on the preopercular margin. Neotypes are designated for Scolopsis japonica and S. curite. Nomenclatural problems, including validity of the genus Scolopsis, are discussed. We regard Scolopsis curite Cuvier, 1815 as a valid binomial name and thus the type species of Scolopsis Cuvier, 1814 by subsequent monotypy.